Role of Sodium nitroprusside on mitigation of salt stress in Sweet corn - Fateme Manshoori; Mohammad Armin; Hamid Marvi (Journal of Research in Biology, 2019)
Effect of salinity and the role of sodium nitroprusside (SNP) on sweet corn was examined as a completely randomized design with three replications in Islamic Azad University of Sabzevar. Factors were sodium nitroprusside at the concentration of 200 ppm (vegetative, reproductive and vegetative + reproductive) and salinity (0,1.5, 3 and 4.5 dS.m-1) during various growth stages. When SNP was applied at vegetative + reproductive stage, the heighest of all the parameters were recorded except carotenoids which was high in the groups treated with SNP at reproductive stage. On the whole, salinity stress imparted the growth of the plant negatively whereas SNP application at vegetative and reproductive stage had better growth effects.